2018
DOI: 10.1902/jop.2017.170249
|View full text |Cite
|
Sign up to set email alerts
|

Salivary neuropeptides, stress, and periodontitis

Abstract: VIP and NPY in saliva could be potential gender-specific salivary biomarkers for periodontitis regardless of psychological stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 48 publications
0
27
0
1
Order By: Relevance
“…Thirdly, among the control group, periodontal patients had higher levels of serum CGRP in comparison with those without periodontitis. Contrary to these results, Haririan and co‐workers observed no differences in CGRP concentrations measured in both serum and saliva of patients with periodontitis and without periodontitis . However, another study showed that periodontally healthy sites showed increased gingival crevicular fluid concentrations of CGRP compared with sites with gingivitis or periodontitis (no detection of CGRP) .…”
Section: Discussionmentioning
confidence: 86%
“…Thirdly, among the control group, periodontal patients had higher levels of serum CGRP in comparison with those without periodontitis. Contrary to these results, Haririan and co‐workers observed no differences in CGRP concentrations measured in both serum and saliva of patients with periodontitis and without periodontitis . However, another study showed that periodontally healthy sites showed increased gingival crevicular fluid concentrations of CGRP compared with sites with gingivitis or periodontitis (no detection of CGRP) .…”
Section: Discussionmentioning
confidence: 86%
“…The EC system can be speculated to mediate a link between stress and periodontitis. Stress is a significant risk factor influencing the immune system and potentially contributing to the progression of periodontitis [46,47]. The EC system plays an essential role in the stress response [48].…”
Section: Discussionmentioning
confidence: 99%
“…EC system can be speculated to mediate a link between stress and periodontitis. Stress is a significant risk factor influencing immune system and potentially contributing to the progression of periodontitis [46,47]. EC system plays an essential role in the stress response [48].…”
Section: Discussionmentioning
confidence: 99%